Isolation of Phytochemical Components Present in Philippine Morinda citrifolia Variety (PhilNONI) - Maslog, Florita S. (Silliman Journal, 2024)
Various modern techniques currently determine phytochemicals, but conventional qualitative tests are still popular for preliminary phytochemical screening of plants. This study was patterned on a previous work of Nagalingam et al. from India, who extracted and did preliminary phytochemical screening of active components in their Indian noni fruit variety. We aimed to isolate the phytochemical components present in our local Morinda citrifolia variety (called PhilNONI by our company). It is a fact that different noni varieties from different countries may differ in phytochemical contents. Recent scientific studies have established a relationship between phytochemicals and health benefits, such as diabetes, cancer, and heart diseases, in boosting immunity and as powerful antioxidants. Phytochemicals, moreover, fulfill the action of cell regeneration in wound healing. There are about 65-200 phytochemicals that can fight diseases, boost energy, and revitalize health. They are powerful innovators, as discussed by Rita Elkins in her book on the Noni Revolution. Using three extracts from noni powder, ethanol, methanol, and water, we isolated qualitatively in appreciable amounts from the three extracts of PhilNONI the following groups of phytochemicals: steroids, cardiac glycosides, terpenoids, alkaloids, carbohydrates, flavonoids, and saponin. Gallic catechol tannin, acidic compounds, and reducing sugar are also in appreciable amounts but only in water extracts. Both ethanol and methanol PhilNONI extracts gave appreciable amounts of phenolic compounds. Protein came out in large amounts from methanol and water extracts and large amounts in ethanol extract, but only for asparagine amino acids. We isolated anthraquinone in medium amounts from methanol extract but in appreciable amounts from ethanol and water extracts. There was no lipid or fat isolated from the three extracts.